2012
DOI: 10.1029/2012jd018542
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized observations of cloud‐to‐ground lightning using VHF broadband interferometer and acoustic arrays

Abstract: [1] A single-station-based lightning discharge channel reconstruction system by combining a two-dimensional (2D) VHF broadband interferometer and a three-dimensional (3D) acoustic lighting mapping system has been developed and used for lightning observations. Two cloud-to-ground (CG) flashes with highly branched leaders recorded by the system are analyzed and presented in this paper. VHF radiation could well delineate the development of simultaneous leader branches, while acoustic emissions mainly located on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
4
8
0
1
Order By: Relevance
“…However, in all cases, the infrasound pulses were located very near the lightning channels as mapped by the LMA. Similar agreement between acoustic and VHF lightning locations have been observed in studies including higher‐frequency acoustic measurements [ Arechiga et al , ; Johnson et al , ; Qiu et al , ]. Second, electrostatic production models of infrasound must make use of charge layers with a thickness of 200–400 m to produce pulses of reasonable duration.…”
Section: Discussionsupporting
confidence: 65%
“…However, in all cases, the infrasound pulses were located very near the lightning channels as mapped by the LMA. Similar agreement between acoustic and VHF lightning locations have been observed in studies including higher‐frequency acoustic measurements [ Arechiga et al , ; Johnson et al , ; Qiu et al , ]. Second, electrostatic production models of infrasound must make use of charge layers with a thickness of 200–400 m to produce pulses of reasonable duration.…”
Section: Discussionsupporting
confidence: 65%
“…Acoustic Data Teer and Few [1974] 17 CG and 20 IC [Arizona storm, also studied in MacGorman et al 1981] MacGorman et al [1981] statistics on three storms: Arizona (26 + 11 flashes), Colorado (35 flashes), and Florida (9 flashes) Arechiga et al [2011] two triggered lightning flashes Johnson et al [2011] at least 24 natural lightning flashes Qiu et al [2012] two natural lightning flashes Bodhika et al [2013] two natural lightning flashes, no comparison with LMA Arechiga et al [2014] two intracloud natural lightning flashes Anderson et al [2014] eight natural lightning flashes camera . The authors found a good agreement between the acoustic reconstructions and the pictures when the discharge is visible, being outside the storm cloud.…”
Section: Authorsmentioning
confidence: 99%
“…Different authors [ Arechiga et al , ; Johnson et al , ; Qiu et al , ; Bodhika et al , ] compared the results of acoustic reconstructions of lightning channels to electromagnetic ones. It is to be noted that all these papers focused on the comparison of reconstructions from acoustic records and VHF sources detected by a LMA.…”
Section: Introductionmentioning
confidence: 99%
“…The actual locating results are similar to those of the existing VHF TDOA (Time Difference of Arrival) lightning locating network.which is much higher than that of the existing TDOA locating system [29]. Although these advantages can only be fully demonstrated when the interferometer is used for azimuth-elevation 2-D direction finding, the high time resolution 2-D locating of the interferometer can be used for networking observation or in combination with another set of lightning locating system to give full play to its characteristics and describe the lightning discharge process in detail [23,30,31]. Currently, the existing lightning interferometers can be roughly divided into two types: narrow-band interferometers and wide-band interferometers, depending on the bandwidth of the received signals [6,32].…”
mentioning
confidence: 99%
“…Especially the continuous interferometer using high-speed Analog to Digital (A/D) data acquisition card at present has a high time resolution, a large dynamic range of signal amplitude resolution and continuous sampling recording ability, making the new interferometer able to describe the lightning discharge processes more completely [29].A single-station broadband interferometer system can only give the locating results of the radiation sources in two dimensions, with which many conclusions can be made based on the estimation. Even if the 3-D information can be estimated by combining the information provided by other synchronous observation systems [22,30,31], there is still an inconvenience and uncertainty in the study of the physical mechanism of discharge. How to use multi-station synchronous 3-D observation to give full play to the advantages of interferometer system is always a problem faced in interferometer observation, and many attempts have been made continuously to overcome this [34][35][36].…”
mentioning
confidence: 99%